Implementasi Aditif Pakan Berbahan Nano Partikel Bawang Tiwai (Eleutherine amaricana Merr) Terhadap Performans Produksi Ayam Broiler: Implementation of Feed Additives Made from Nano Particles of Tiwai Onion (Eleutherine amaricana Merr) on Chicken Production Performance - Manullang, Julinda Romauli; Simanjuntak, Servis; Hidayat, M. Nur (Fakultas Peternakan Universitas Jambi, 2025)
Background: Broiler chickens, a type of poultry, are utilized as a relatively cheaper and easily accessible source of high-quality animal protein. Increasing livestock productivity requires an effort to find alternative feed sources. Feed is produced in large quantities and contains high nutrients. An alternative that can be used is to utilise local feed ingredients that contain tiwai onion (Eleutherine americana Merr). Purpose: The objective of this study was to ascertain the optimal concentration of Tiwai onion nano particles and how their feeding to broiler chickens affects broiler performance. Methods: Using a completely randomised complete block design (CRD), this study included five replicates and five treatments, each consisting of 4 broilers and reared until 35 days of age. Feed consumption, body weight gain, feed conversion, final body weight, and mortality were the parameters of the study. Onion tiwai nanoparticles were administered at P0 which is the control or without the administration of nano particles. P1 0.2%, P2 0.4%, P3 0.6% and P4 (0.8%) contained tiwai onion. The data obtained were analysed using One Way Anova followed by Duncan's Test to examine the values of feed consumption, body weight gain, feed conversion, final body weight, and mortality. Results: The study showed that the administration of tiwai onion nanoparticles had no significant effect (P>0.05) on feed consumption, body weight gain, feed conversion, final body weight and mortality. Conclusion: Giving tiwai onion nanoparticles as a feed additive at a dose of 0.2% - 0.8% / kg had no significant effect on feed consumption, FCR, PBB, final body weight and mortality. Giving nano particles of tiwai onions is able to maintain health in livestock because the content of tiwai onions as a feed additive is able to increase the immune system antiviral, and as well as anti-bacterial which can reduce bacterial growth so that the mortality rate in the study was 0% or no deaths.